2017
DOI: 10.1161/jaha.117.006394
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase‐4 Regulates Hematopoietic Stem Cell Activation in Response to Chronic Stress

Abstract: BackgroundDPP4 (Dipeptidyl peptidase‐4)‐GLP‐1 (glucagon‐like peptide‐1) and its receptor (GLP‐1R) axis has been involved in several intracellular signaling pathways. The Adrβ3 (β3‐adrenergic receptor)/CXCL12 (C‐X‐C motif chemokine 12) signal was required for the hematopoiesis. We investigated the novel molecular requirements between DPP4‐GLP‐1/GLP‐1 and Adrβ3/CXCL12 signals in bone marrow (BM) hematopoietic stem cell (HSC) activation in response to chronic stress.Methods and ResultsMale 8‐week‐old mice were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 38 publications
(69 reference statements)
6
42
0
Order By: Relevance
“…We have shown that chronic stress markedly suppressed the plasma corticosterone level; this effect was restored by the treatment with anagliptin and exenatide. Recently, we have demonstrated that chronic stress also increased plasma adrenaline and noradrenaline levels, and these changes were reversed by both drugs . In addition, our observations here show that pharmacological interventions targeted toward DPP4 activity and GLP‐1R activation ameliorated the levels of plasma glucose and adipose insulin receptor substrate 1 and glucose transporter 4 genes in the stressed mice.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…We have shown that chronic stress markedly suppressed the plasma corticosterone level; this effect was restored by the treatment with anagliptin and exenatide. Recently, we have demonstrated that chronic stress also increased plasma adrenaline and noradrenaline levels, and these changes were reversed by both drugs . In addition, our observations here show that pharmacological interventions targeted toward DPP4 activity and GLP‐1R activation ameliorated the levels of plasma glucose and adipose insulin receptor substrate 1 and glucose transporter 4 genes in the stressed mice.…”
Section: Discussionsupporting
confidence: 67%
“…The luminescence intensity was calculated using a luminometer. Based on the standard curve, the plasma and tissue DPP4 levels were derived to represent as ng/mL . All measurements were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A recent study reported that individuals with and without diabetes mellitus had increased plasma DPP4 levels and decreased plasma GLP-1 levels. 21 In mice and rats, chronic stress increased plasma and tissue DPP4 activities and decreased plasma and brain GLP-1 levels, 22 suggesting an imbalance between DPP4 and GLP-1 as a potential therapeutic target in the management of vascular aging and atherosclerosis in animals under experimental stress conditions.…”
mentioning
confidence: 99%
“…Chronic variable stress has been shown to produce harmful changes in plasma and tissue DPP4 levels. 22,23 It is established that inflammation participates in all stages of atherosclerosis, including initiation, progression, and ultimately, the thrombotic complications. 24 Data from our research and those from other groups clearly demonstrated that chronic variable stress activated bone-marrow hematopoietic stem cell proliferation via the inactivation if β-adrenergic receptor-mediated C-X-C motif chemokine 12 (CXCL12), leading to an increased output of neutrophils and inflammatory monocytes.…”
mentioning
confidence: 99%